2016
DOI: 10.1631/jzus.b1500180
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of prokineticin receptor (PKR1 rs4627609 and PKR2 rs6053283) and recurrent pregnancy loss

Abstract: Recurrent pregnancy loss (RPL) is a condition with complex etiologies, to which both genetic and environmental factors may contribute. During the last decade, studies indicated that the expression patterns of the prokineticin receptor (PKR1 and PKR2) are closely related to early pregnancy. However, there are few studies on the role of PKR1 and PKR2 in RPL. In this study, we purpose to investigate the association between polymorphisms of the prokineticin receptor (PKR1 rs4627609 and PKR2 rs6053283) and RPL on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
“…A common polymorphism at codon 72 (Pro72Arg) in the p53 gene was related to the occurrence of iRPL 90,91 . However, some variants in the TP73 gene—such as rs2273953, rs1801173 20 ; rs4627609 in PKR1 gene 24 ; Intron 16 I/D 33 ; rs1799752 92 and rs1042838 in PGR gene 47 have not been associated with pregnancy loss.…”
Section: Resultsmentioning
confidence: 99%
“…The pkr2 gene is located in a region highly susceptible to mutations, as shown by linkage analysis studies and confirmed by the existence of several polymorphisms of the pkr2 gene associated with some diseases. Thus, the pkr2 polymorphism rs6053283 has been detected in idiopathic and recurrent pregnancy loss [18,19]. The presence of this rs6053283 polymorphism alters the exonic splicing enhancer (ESE) motif, which is recognized by serine/arginine-rich (SR) proteins that may be involved in the PKR2 splicing mechanism [18,19].…”
Section: Genetic and Splicing Variantsmentioning
confidence: 99%
“…Thus, the pkr2 polymorphism rs6053283 has been detected in idiopathic and recurrent pregnancy loss [18,19]. The presence of this rs6053283 polymorphism alters the exonic splicing enhancer (ESE) motif, which is recognized by serine/arginine-rich (SR) proteins that may be involved in the PKR2 splicing mechanism [18,19]. pkr2 gene polymorphisms have also been described in depressive and bipolar disorders and methamphetamine addiction in the Japanese population [20].…”
Section: Genetic and Splicing Variantsmentioning
confidence: 99%
“…Similarly, a case-control study found that the rs1870377 (1719A/T) polymorphism in the vascular endothelial growth factor receptor 2 (VEGFR-2 or KDR) is significantly associated with iRPL and may be a factor in disease susceptibility [32]. Cao et al found that the rs6053283 polymorphism Prokineticin receptor 2 (PKR2), a receptor for the endocrine gland-derived vascular endothelial growth factor 2, was significantly associated with iRPL in the Chinese Han population probably due to its role in angiogenesis during pregnancy [33]. Additionally, meta-analysis studies have shown that rs1042522 (p53 Arg72Pro or p53 codon 72) polymorphisms in the TP53 gene (another gene related to angiogenesis and embryo development) are related to the occurrence of iRPL [31,34].…”
Section: Genetic Variants Can Alter Correct Tissue Formation and Remomentioning
confidence: 99%